MINAT BELI KONSUMEN DITINJAU DARI STORE ATMOSPHERE, CITA RASA DAN WORD OF MOUTH DI MIE GACOAN SOLO RAYA - Dwi Kurnia Sari; Supawi Pawenang (JURNAL ILMIAH EDUNOMIKA, 2020)
This study aims to determine the effect simultaneously and partially on consumer buying interest on store atmosphere, taste of food, and word of mouth at Mie Gacoan Solo Raya. The method used is a quantitative method. Data collection techniques were carried out by distributing questionnaires to respondents. The population in this study were consumers of Mie Gacoan Solo Raya. The sampling technique used non-probability techniques with accindental sampling.The data analysis used was validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis, F test, t test, and R2 with the help of SPSS version-20. Based on the results of the data calculation and analysis used, the regression equation is obtained, namely Y = 2.697+ 0.609X1 0.160X2 + 0.126X3 + e. This equation shows that consumer buying interest is influenced by store atmosphere, taste, and word of mouth. The conclusion that can be drawn is: "There is a simultaneous influence of store atmosphere, taste of food, and word of mouth on consumer buying interest at Mie Gacoan Solo Raya" can be accepted. "There is an effect of store atmosphere on consumer purchase interest at Mie Gacoan Solo Raya" is acceptable. "There is an influence of taste of food on consumer buying interest in Mie Gacoan Solo Raya" is acceptable. "There is an effect of word of mouth on consumer buying interest at Mie Gacoan Solo Raya" is acceptable. The result of the coefficient of determination R2 is 0.736, which means that 73.6% of the variation in the purchase interest variable can be explained by the store atmosphere, taste of food, and word of mouth variables, while the rest is explained by other variables not included in this study. Keywords : Store Atmosphere, Taste of Food, Word of Mouth and Consumer Buying Interest.